Neoliberalist influences on nursing hospital work process and organization - Norma Valéria Dantas de Oliveira Souza; Francisco Gleidson de Azevedo Gonçalves; Ariane da Silva Pires; Helena Maria Scherlowski Leal David
ABSTRACT Objectives: To describe and analyze the influence of the neoliberal economic and political model on the nursing hospital work process and organization. Method: Qualitative descriptive research, having as its scenery a university hospital. The subjects were 34 nursing workers. The data collection took place from March to July 2013, through semi-structured interview. The data treatment technique used was content analysis, which brought up the following category: working conditions precariousness and its consequences to the hospital work process and organization in the neoliberal context. Results: The consequences of neoliberalism on hospital work process and organization were highlighted, being observed physical structure, human resources and material inadequacies that harms the assistance quality. In addition to wage decrease that cause the need of second jobs and work overload. Final considerations: There is a significant influence of the neoliberal model on hospital work, resulting on working conditions precariousness.